2008
DOI: 10.1017/s0033291708003644
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in recently discharged psychiatric patients: a case-control study

Abstract: The weeks after discharge from psychiatric care represent a critical period for suicide risk. Measures that could reduce risk include intensive and early community follow-up. Assessment of risk should include established risk factors as well as current mental state and there should be clear follow-up procedures for those who have self-discharged. Recent detention under the Mental Health Act and current use of enhanced levels of aftercare may be protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
2
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(143 citation statements)
references
References 23 publications
9
125
2
7
Order By: Relevance
“…SMR was highest in the first year (11.1), and dropped incrementally with time. Studies have shown that risk is especially high in the post-psychotic phase of recovery, soon after discharge from hospital (Hunt et al, 2009;Rossau & Mortensen, 1997). Reasons for this are hypothesised to be connected with the realisation of loss of role and function, the frustrations associated with the recovery process, and difficulties with everyday activities (Power & McGowan, 2011).…”
Section: Prevalence Of Suicide and Dsh In Psychosismentioning
confidence: 99%
“…SMR was highest in the first year (11.1), and dropped incrementally with time. Studies have shown that risk is especially high in the post-psychotic phase of recovery, soon after discharge from hospital (Hunt et al, 2009;Rossau & Mortensen, 1997). Reasons for this are hypothesised to be connected with the realisation of loss of role and function, the frustrations associated with the recovery process, and difficulties with everyday activities (Power & McGowan, 2011).…”
Section: Prevalence Of Suicide and Dsh In Psychosismentioning
confidence: 99%
“…For selvmordstruede pasienter er tiden like etter utskrivelse fra psykiatrisk sykehus saerlig risikofylt med tanke på selvmordsfare (Hunt et al, 2009;Qin & Nordentoft, 2005).…”
Section: Innledningunclassified
“…Kontinuitet i helsetjenestilbudet etter utskrivelse kan vaere livreddende (Hunt, et al, 2009). For ivaretakelse av pasienten i den sårbare overgangsfasen etter utskrivelse anbefaler Nasjonale retningslinjer for selvmordsforebygging i psykisk helsevern (retningslinjen): «Når selvmordsrisiko har vaert en problemstilling under oppholdet eller tidligere bør selvmordsrisikoen vurderes og dokumenters ved utskriving fra døgnenhet.…”
Section: Innledningunclassified
“…También existe relación entre suicidio y trastornos de alimentación en adolescentes mujeres, trastornos de conducta en hombres (límite y sociópata) y abuso de sustancias en ambos sexos (Bhatia & Bhatia, 2007 Existe mayor riesgo de suicidio en los primeros meses después de ser diagnosticado con algún trastorno afectivo (Castro-Díazet al, 2013), depresión psicótica y trastorno bipolar (Steele & Doey, 2007). El riesgo aumenta en los primeros días o semanas de inicio de un tratamiento farmacológico ya que en dicho período suele empeorar la sintomatología (Healy & Alfred, 2005;Perlis et al, 2007), y en los días siguientes al alta hospitalaria, sobre todo en aquellos que consultan en urgencias (Gairin, House, & Owens, 2003;Hansagi, Olsson, Hussain, & Onlén, 2008), reportando un riesgo 100 veces mayor (Ho, 2003) entre los tres días y la semana después de salir del hospital (Hunt et al, 2009). …”
Section: Asociación Entre Suicidio Y Trastorno Mentalunclassified